The persuasive speech in rhetoric and tales (Training and Practice : Journal of Educational Sciences, 2018)
Although the original sitation of rhetorical speech and the speech in tales bears resemblance with each other (mutual attention of the speaker and the audience, the aesthetic formation of the speech), in my presentation I aim to analyse the difference between the two, in the correlation of persuasion. In rhetoric it means the deliberate use of certain formations to achieve the desired effect on the audience. The basis of persuasion is the acceptance of probability. The tale can be interpreted as a meaning revelation in the hermeneutic progress of understanding, which presupposes the equal inclusion both the speaker and the listener. In this case the speech embodies the world-like presence of language. In conclusion, these two methods of persuasion are in relationship with the deeper disparities of aesthetic impression and aesthetic recognition.